A case of synchronous multiple bilateral breast cancer after breast augmentation - Yamamoto, Shinya (Springerplus, 2015)
Breast cancer after breast augmentation is not rare, but cases of bilateral breast cancer after augmentation are not often reported. A 43-year-old woman attended our hospital because of a mass in her left breast. She had undergone breast augmentation by implants 4 years before at a cosmetic surgery clinic. There were operative scars in her bilateral axilla. A detailed examination revealed bilateral breast cancer, and we performed nipple-sparing mastectomy in both breasts. Sentinel lymph node biopsy using dye was performed and it identified stained lymph nodes on both sides. The sentinel lymph node biopsy was negative for metastasis on both sides, so axillary lymph node dissection was not performed.